Integrative Regeneration of Articular Cartilage Using Mesenchymal Stem Cells and Gene Therapy: A Precision Medicine Approach - Deby Susanti Pada Vinski Vinski; Natasha Cinta Vinski; Andi Kurniawan Nugroho; Sunaryo Kusumo; Darren Karl Griffin (Journal of World Science, 2026)
Osteoarthritis (OA) is a prevalent and debilitating chronic condition that primarily affects the articular cartilage, leading to pain, stiffness, and loss of function. Despite significant advancements in understanding its pathophysiology, an effective cure remains elusive. This paper explores the integrative regeneration of articular cartilage using mesenchymal stem cells (MSCs) combined with gene therapy as a precision medicine approach. MSCs are particularly promising due to their chondrogenic potential and ability to repair damaged cartilage. However, the inflammatory environment in OA often limits the survival of MSCs. Gene therapy emerges as a solution to modulate this environment, enhancing the regenerative capacity of MSCs. This study highlights the synergy between MSC therapy and gene therapy in promoting cartilage repair, focusing on the Vinski protocol. By targeting the joint's microenvironment and using MSCs in combination with gene therapy, this integrated approach aims to provide a more effective treatment for OA. The application of gene therapy is expected to not only sustain MSC survival but also improve their therapeutic effects, making this method a promising avenue for OA treatment.